A novel Xp22.13 microdeletion in Nance‐Horan syndrome. Issue 11 (2nd May 2017) - Accogli, Andrea; Traverso, Monica; Madia, Francesca; Bellini, Tommaso; Vari, Maria Stella; Pinto, Francesca; Capra, Valeria
Abstract : Background: Nance‐Horan syndrome (NHS) is a rare X‐linked developmental disorder characterized by congenital cataract, dental anomalies and facial dysmorphisms. Notably, up to 30% of NHS patients have intellectual disability and a few patients have been reported to have congenital cardiac defects. Nance‐Horan syndrome is caused by mutations in the NHS gene that is highly expressed in the midbrain, retina, lens, tooth, and is conserved across vertebrate species. Although most pathogenic mutations are nonsense mutations, a few genomic rearrangements involving NHS locus have been reported, suggesting a possible pathogenic role of the flanking genes. Methods: Here, we report a microdeletion of 170, 6 Kb at Xp22.13 (17.733.948‐17.904.576) (GRCh37/hg19), detected by array‐based comparative genomic hybridization in an Italian boy with NHS syndrome. Results: The microdeletion harbors the NHS, SCLML1, and RAI2 genes and results in a phenotype consistent with NSH syndrome and developmental delay. Conclusion: We compare our case with the previous Xp22.13 microdeletions and discuss the possible pathogenetic role of the flanking genes. Birth Defects Research 109:866–868, 2017. © 2017 Wiley Periodicals, Inc.